Impact of Socio-cultural Business Environment on Entrepreneurial Intention: A Study among Nepalese Muslim Community - Rashesh Vaidya; Nikita Lohani; Parshuma Lacoul (Journal of Business and Management Review, 2022)
Muslims in Nepal historically originated from the Indian subcontinent, mainly from India, and from Tibet. Kashmiri Muslim traders first arrived at Kathmandu Valley during King Ratna Malla Regime (1484-1520 AD) and then followed by Afghans, Persians, and even Arabian. Finally, the Tibetan Muslims entered Nepal after being displaced from China. The Muslims from India migrated to the Terai region of Nepal after invasion of British in India. The Muslims in Nepal are seen as highly integrated with the Hindu communities as well as the business they are doing are related to the Hindu community. The main purpose of the earlier migration of the Muslim community in Nepal was basically to establish or run a business. Hence, the paper tries to find out the impact of the socio-cultural business environment on entrepreneurial intention among the Nepalese Muslim community. The paper has taken a sample of 180 Nepalese Muslims. The paper found that the people from Nepalese Muslim community are not highly educated. The major communicating language of the community is seen as Nepali. Under socio-culture factors, the respondents stressed that education could play a vital role in enhancing their entrepreneurial quality. Similarly, parents are seen as role models among the community to embrace self-employment. Religious and social system factors are not seen as influencing factors in enhancing entrepreneurial intentions among the Nepalese Muslim community.